Bahasa Inggris - Fitriani, Fitriani; Feranie, Selly; Samsudin, Achmad; Aviyanti, Lina (EduFisika: Jurnal Pendidikan Fisika, 2025)
The ability to think critically and solve complex problems requires a deep understanding of physics concepts. This study employed a novel method to conduct a multidimensional analysis of students' conceptual understanding of Newton's Laws using conceptual tests designed to assess indicators of interpretation, exemplification, inference, comparison, explanation, and integration. This study addresses conceptual understanding as a whole and in a controlled manner, and the action learning approach can support it. The sample in this study consisted of 25 students of class XII 1 at a high school in Kupang City, NTT. This study used a quantitative descriptive method with a cross-sectional approach. The results showed that the average understanding score of students as a whole was in the “very low” category, namely 28.4%. Two main weaknesses were also found in students: (1) students showed a better understanding of Newton’s First Law compared to the Second Law (29.6%) and the Third Law (22.4%) which were more applicable, and (2) “Comparing” was the lowest indicator (21%). Meanwhile, based on gender, it showed that female students excelled in the “inferencing” indicator, while male students excelled in the “exemplifying” indicator. The results of this study indicate that learning methods that are mostly focused on lectures and abstract physics concepts can hinder conceptual understanding, as well as analytical and comparative skills. Therefore, this study recommends the implementation of an experiment-based learning approach to improve students' practical experience and conceptual understanding, as well as relate it to analytical indicators and Newton's Second and Third Laws.